Sole material, sports shoe sole and sports shoe
By using matrix materials such as natural rubber and butyl rubber in the sole material, combined with functional additives such as sulfur and carbon black, and co-advancers that connect strong adjusters and doped whiskers, the existing sole has been solved through specific treatment methods. The problem of poor anti-slip performance of the material and low temperature resistance and insufficient bending stability achieve better coordination of elasticity, wear resistance and anti-slip performance.
Patent Information
- Application Number
- CN202411328153.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing sole materials have poor anti-slip properties, difficult to coordinate elasticity, wear resistance and anti-slip properties, and insufficient low temperature resistance and bending stability, which limits the efficiency of sports shoes.
Using natural rubber and butyl rubber as matrix material, sulfur, carbon black, stearic acid, zinc oxide, anti-aging agent DPPD, accelerator TMDM, and co-promoting agents that combine strong adjusters and dopant whiskers, through specific treatment Methods optimize material performance, including oscillation, ball milling and blending and stirring treatment, to improve the elasticity, wear resistance and anti-slip properties of the material.
It significantly improves the coordination of elasticity, wear resistance and anti-slip properties of the sole material, and improves the product's low temperature resistance and bending stability, improving the overall performance of sports shoes.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shoes, in particular to a sole material, a sports shoe sole and a sports shoe. Background Art
[0002] Sports shoes are a type of footwear designed specifically for various sports activities, which have the functions of protecting the feet, providing comfort and enhancing sports performance. The design and materials of sports shoes vary according to the type of sports and the needs of users, such as running shoes, basketball shoes, football shoes, etc., to provide the best support and protection. Modern sports shoes are usually also fashionable and personalized to meet the needs and tastes of different consumers.
[0003] Existing sole materials have poor anti-slip performance, and it is difficult to coordinate and improve the elasticity, wear resistance and anti-slip performance of the sole materials, which limits the use efficiency of the product. The product's low temperature resistance and bending stability are poor, which further limits the use efficiency of the product. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a sole material, a sports shoe sole and a sports shoe to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a sole material, comprising the following raw materials in parts by weight:
[0007] 35-40 parts of natural rubber, 25-30 parts of butadiene rubber, 7-11 parts of continuous strength adjuster, 4-7 parts of whisker-doped synergist, 3-5 parts of sulfur, 1-3 parts of carbon black, 1-3 parts of stearic acid, 1-3 parts of zinc oxide, 2-4 parts of antioxidant DPPD, and 2-4 parts of accelerator TMDM.
[0008] Preferably, the sole material comprises the following raw materials in parts by weight:
[0009] 37.5 parts of natural rubber, 27.5 parts of butadiene rubber, 9 parts of continuous strength adjuster, 5.5 parts of whisker-doped synergist, 4 parts of sulfur, 2 parts of carbon black, 2 parts of stearic acid, 2 parts of zinc oxide, 3 parts of antioxidant DPPD, and 3 parts of accelerator TMDM.
[0010] Preferably, the preparation method of the continuous strong effect agent is:
[0011] S01: The flaky talc is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 350-400 W for 20-30 min. After the oscillation is completed, the flaky talc is washed with water, filtered and dried to obtain a dry flaky talc;
[0012] S02: 4-7 parts of dry flaky talc, 1-3 parts of urea, 2-3 parts of nano-silica sol and 5-8 parts of 5-7% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier;
[0013] S03: The flaky talcum powder modifier and the continuous effect regulating liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 1-2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous effect regulating agent.
[0014] Preferably, the mixing and stirring process has a stirring speed of 450-550 r / min, a stirring time of 35-45 min, and a stirring temperature of 50-55° C.
[0015] Preferably, the continuous effect regulating solution comprises the following raw materials in parts by weight:
[0016] 3~5 parts of boron nitride powder, 4~7 parts of yttrium nitrate solution, 2~5 parts of sodium silicate solution, 2~4 parts of glass fiber and 1~2 parts of sodium carboxymethyl cellulose.
[0017] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium silicate solution is 4-6%.
[0018] Preferably, the preparation method of the whisker-doped synergist is:
[0019] S101: irradiating the nano-silicon dioxide in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed;
[0020] Fully blend 2-5 parts of irradiated nano-silica, 1-3 parts of silane coupling agent KH560, 2-3 parts of nano-bentonite and 4-7 parts of chitosan solution by weight to obtain a nano-silica synergistic solution;
[0021] S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution;
[0022] S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1500-1700 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
[0023] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-6%.
[0024] A sports shoe sole is made of the above-mentioned sole material and is made into the sports shoe sole through existing banburying, mixing, extrusion and mold vulcanization molding technology.
[0025] The present invention also provides a sports shoe comprising the above-mentioned sports shoe sole.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The sole material of the present invention adopts natural rubber and butadiene rubber as the base material, and optimizes the performance effect of the product by adding sulfur, carbon black, stearic acid, zinc oxide, antioxidant DPPD, and accelerator TMDM as functional additives. At the same time, the added continuous strength adjuster and the synergist of doped whiskers are coordinated and coordinated, and the elasticity, wear resistance and anti-skid performance of the prepared sole material are coordinated and improved, and the product has remarkable effects on low temperature resistance and bending stability;
[0028] 2. Lianqiang effective adjuster uses flaky talc treated with potassium permanganate solution to optimize the active efficiency of flaky talc. At the same time, it is mixed and stirred with urea, nano-silica sol and 5-7% sodium lignin sulfonate solution by mass fraction to optimize the coordination and improvement effect of flaky talc and Lianqiang effective adjuster, and improve the efficiency of the coordination and synergistic effect of the two. Lianqiang effective adjuster is blended with boron nitride powder, yttrium nitrate solution, sodium silicate solution, glass fiber and sodium carboxymethyl cellulose. Through the mutual coordination and coordination between the raw materials, boron nitride and glass fiber are used as the matrix agent, and needle-shaped glass fiber is used to coordinate the flaky talc. Through the coordination and coordination between the raw materials in Lianqiang effective adjuster, the coordination of the elasticity, wear resistance and anti-slip performance of the product in the system is enhanced, and the low temperature resistance and bending stability of the product are improved;
[0029] 3. The whisker-doped synergist uses nano-silica that is irradiated in a proton irradiation box before irradiating to stimulate the active performance of the nano-silica. At the same time, the silane coupling agent KH560, nano-bentonite and 4-chitosan solution are fully blended to obtain a nano-silica synergistic liquid. Nano-bentonite is used as a lamellar structure and interspersed in the system. The high specific surface area of nano-silica is combined to enhance the interface and stability of the system. At the same time, the silicon carbide whiskers and lanthanum nitrate solution are mixed and stirred evenly to enhance the dispersion activity of the whiskers, so that the silicon carbide whisker liquid and the nano-silica synergistic liquid can be better coordinated and synergized, thereby enhancing the synergistic effect with the continuous strong adjusting agent, further improving the coordination of the product's elasticity, wear resistance and anti-slip performance, and further improving the product's low temperature resistance and bending stability. DETAILED DESCRIPTION
[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] A shoe sole material of this embodiment includes the following raw materials in parts by weight:
[0032] 35-40 parts of natural rubber, 25-30 parts of butadiene rubber, 7-11 parts of continuous strength adjuster, 4-7 parts of whisker-doped synergist, 3-5 parts of sulfur, 1-3 parts of carbon black, 1-3 parts of stearic acid, 1-3 parts of zinc oxide, 2-4 parts of antioxidant DPPD, and 2-4 parts of accelerator TMDM.
[0033] The sole material of this embodiment includes the following raw materials in parts by weight:
[0034] 37.5 parts of natural rubber, 27.5 parts of butadiene rubber, 9 parts of continuous strength adjuster, 5.5 parts of whisker-doped synergist, 4 parts of sulfur, 2 parts of carbon black, 2 parts of stearic acid, 2 parts of zinc oxide, 3 parts of antioxidant DPPD, and 3 parts of accelerator TMDM.
[0035] The preparation method of the continuous strong effect agent of this embodiment is:
[0036] S01: The flaky talc is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 350-400 W for 20-30 min. After the oscillation is completed, the flaky talc is washed with water, filtered and dried to obtain a dry flaky talc;
[0037] S02: 4-7 parts of dry flaky talc, 1-3 parts of urea, 2-3 parts of nano-silica sol and 5-8 parts of 5-7% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier;
[0038] S03: The flaky talcum powder modifier and the continuous effect regulating liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 1-2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous effect regulating agent.
[0039] The stirring speed of the blending and stirring process in this embodiment is 450-550 r / min, the stirring time is 35-45 min, and the stirring temperature is 50-55° C.
[0040] The continuous effect regulating solution of this embodiment comprises the following raw materials in parts by weight:
[0041] 3~5 parts of boron nitride powder, 4~7 parts of yttrium nitrate solution, 2~5 parts of sodium silicate solution, 2~4 parts of glass fiber and 1~2 parts of sodium carboxymethyl cellulose.
[0042] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 4-6%.
[0043] The preparation method of the whisker-doped synergist of this embodiment is as follows:
[0044] S101: irradiating the nano-silicon dioxide in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed;
[0045] Fully blend 2-5 parts of irradiated nano-silica, 1-3 parts of silane coupling agent KH560, 2-3 parts of nano-bentonite and 4-7 parts of chitosan solution by weight to obtain a nano-silica synergistic solution;
[0046] S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution;
[0047] S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1500-1700 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
[0048] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-6%.
[0049] A sports shoe sole of the present embodiment is made of the above-mentioned sole material.
[0050] A sports shoe of this embodiment includes the above-mentioned sports shoe sole.
[0051] Embodiment 1: A shoe sole material, comprising the following raw materials in parts by weight:
[0052] 35 parts of natural rubber, 25 parts of butadiene rubber, 7 parts of continuous strength adjuster, 4 parts of whisker-doped synergist, 3 parts of sulfur, 1 part of carbon black, 1 part of stearic acid, 1 part of zinc oxide, 2 parts of antioxidant DPPD, and 2 parts of accelerator TMDM.
[0053] The preparation method of the continuous strong effect agent of this embodiment is:
[0054] S01: The flaky talc powder is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 350 W for 20 minutes. After the oscillation is completed, the flaky talc powder is washed with water, filtered, and dried to obtain a dry flaky talc powder;
[0055] S02: 4 parts of dry flaky talc, 1 part of urea, 2 parts of nano-silica sol and 5 parts of 5% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier;
[0056] S03: The flaky talcum powder modifier and the continuous effect regulating liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a continuous effect regulating agent.
[0057] The stirring speed of the blending and stirring process in this embodiment is 450 r / min, the stirring time is 35 min, and the stirring temperature is 50°C.
[0058] The continuous effect regulating solution of this embodiment comprises the following raw materials in parts by weight:
[0059] 3 parts of boron nitride powder, 4 parts of yttrium nitrate solution, 2 parts of sodium silicate solution, 2 parts of glass fiber and 1 part of sodium carboxymethyl cellulose.
[0060] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 4%.
[0061] The preparation method of the whisker-doped synergist of this embodiment is as follows:
[0062] S101: irradiating the nano-silicon dioxide in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed;
[0063] 2 parts of irradiated nano-silica, 1 part of silane coupling agent KH560, 2 parts of nano-bentonite and 4 parts of chitosan solution are fully mixed by weight to obtain a nano-silica synergistic solution;
[0064] S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution;
[0065] S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
[0066] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the lanthanum nitrate solution is 4%.
[0067] A sports shoe sole of the present embodiment is made of the above-mentioned sole material.
[0068] A sports shoe of this embodiment includes the above-mentioned sports shoe sole.
[0069] Embodiment 2: A shoe sole material, comprising the following raw materials in parts by weight:
[0070] 40 parts of natural rubber, 30 parts of butadiene rubber, 11 parts of continuous strength adjuster, 7 parts of whisker-doped synergist, 5 parts of sulfur, 3 parts of carbon black, 3 parts of stearic acid, 3 parts of zinc oxide, 4 parts of antioxidant DPPD, and 4 parts of accelerator TMDM.
[0071] The preparation method of the continuous strong effect agent of this embodiment is:
[0072] S01: The flaky talc powder is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 400 W for 30 minutes. After the oscillation is completed, the flaky talc powder is washed with water, filtered, and dried to obtain a dry flaky talc powder;
[0073] S02: 7 parts of dry flaky talc, 3 parts of urea, 3 parts of nano-silica sol and 8 parts of 7% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier;
[0074] S03: The flaky talcum powder modifier and the continuous effect regulating liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1500r / min for 2h. After the ball milling is completed, the mixture is washed with water and dried to obtain a continuous strong effect regulating agent.
[0075] The stirring speed of the blending and stirring process in this embodiment is 550 r / min, the stirring time is 45 min, and the stirring temperature is 55°C.
[0076] The continuous effect regulating solution of this embodiment comprises the following raw materials in parts by weight:
[0077] 5 parts of boron nitride powder, 7 parts of yttrium nitrate solution, 5 parts of sodium silicate solution, 4 parts of glass fiber and 2 parts of sodium carboxymethyl cellulose.
[0078] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 6%.
[0079] The preparation method of the whisker-doped synergist of this embodiment is as follows:
[0080] S101: irradiating the nano-silicon dioxide in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed;
[0081] 5 parts of irradiated nano-silica, 3 parts of silane coupling agent KH560, 3 parts of nano-bentonite and 7 parts of chitosan solution are fully mixed by weight to obtain a nano-silica synergistic solution;
[0082] S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution;
[0083] S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1700 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
[0084] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the lanthanum nitrate solution is 6%.
[0085] A sports shoe sole of the present embodiment is made of the above-mentioned sole material.
[0086] A sports shoe of this embodiment includes the above-mentioned sports shoe sole.
[0087] Embodiment 3: A shoe sole material, comprising the following raw materials in parts by weight:
[0088] 37.5 parts of natural rubber, 27.5 parts of butadiene rubber, 9 parts of continuous strength adjuster, 5.5 parts of whisker-doped synergist, 4 parts of sulfur, 2 parts of carbon black, 2 parts of stearic acid, 2 parts of zinc oxide, 3 parts of antioxidant DPPD, and 3 parts of accelerator TMDM.
[0089] The preparation method of the continuous strong effect agent of this embodiment is:
[0090] S01: The flaky talc powder is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 370 W for 25 minutes. After the oscillation is completed, the flaky talc powder is washed with water, filtered and dried to obtain a dry flaky talc powder;
[0091] S02: 5.5 parts of dry flaky talc, 2 parts of urea, 2.5 parts of nano-silica sol and 6.5 parts of 6% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier;
[0092] S03: The flaky talcum powder modifier and the continuous effect regulating liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1250 r / min for 1.5 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a continuous effect regulating agent.
[0093] The stirring speed of the blending and stirring process in this embodiment is 500 r / min, the stirring time is 40 min, and the stirring temperature is 52.5°C.
[0094] The continuous effect regulating solution of this embodiment comprises the following raw materials in parts by weight:
[0095] 4 parts of boron nitride powder, 5 parts of yttrium nitrate solution, 3.5 parts of sodium silicate solution, 3 parts of glass fiber and 1.5 parts of sodium carboxymethyl cellulose.
[0096] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 5%.
[0097] The preparation method of the whisker-doped synergist of this embodiment is as follows:
[0098] S101: irradiating the nano-silicon dioxide in a proton irradiation box for 12.5 minutes at an irradiation power of 370 W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed;
[0099] 3.5 parts of irradiated nano-silica, 2 parts of silane coupling agent KH560, 2.5 parts of nano-bentonite and 5.5 parts of chitosan solution are fully mixed by weight to obtain a nano-silica synergistic solution;
[0100] S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution;
[0101] S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1600 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
[0102] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the lanthanum nitrate solution is 5%.
[0103] A sports shoe sole of the present embodiment is made of the above-mentioned sole material.
[0104] A sports shoe of this embodiment includes the above-mentioned sports shoe sole.
[0105] Comparative Example 1:
[0106] The difference from Example 3 is that no strong effect agent is added.
[0107] Comparative Example 2:
[0108] The difference from Example 3 is that in the preparation of the Lianqiangxiao adjusting agent, the flaky talc modifier is replaced by flaky talc.
[0109] Comparative Example 3:
[0110] The difference from Example 3 is that the preparation method of the flaky talc modifier is different. 5.5 parts of flaky talc and 6.5 parts of 6% by mass sodium lignin sulfonate solution are blended and stirred. The stirring speed of the blending and stirring treatment is 500 r / min, the stirring time is 40 min, and the stirring temperature is 52.5 ° C. After stirring, the mixture is washed with water, filtered, and dried to obtain a flaky talc modifier.
[0111] Comparative Example 4:
[0112] The difference from Example 3 is that the continuous effect regulating liquid treatment was not used in the preparation of the continuous strong effect regulating agent.
[0113] Comparative Example 5:
[0114] The difference from Example 3 is that no synergist for doping whiskers is added.
[0115] Comparative Example 6:
[0116] The difference from Example 3 is that the nano-silicon dioxide synergistic liquid treatment is not used in the preparation of the synergistic agent for doped whiskers.
[0117] Comparative Example 7:
[0118] The difference from Example 3 is that no irradiated nano-silicon dioxide is added in the preparation of the nano-silicon dioxide co-advancing solution.
[0119] Comparative Example 8:
[0120] The difference from Example 3 is that no nano-bentonite is added in the preparation of the nano-silicon dioxide synergistic solution.
[0121] Comparative Example 9:
[0122] The difference from Example 3 is that the silane coupling agent KH560 is not added in the preparation of the nano-silica synergistic solution, and deionized water is used instead of the chitosan solution.
[0123] Comparative Example 10:
[0124] The difference from Example 3 is that the silicon carbide whisker liquid treatment is not used in the preparation of the whisker-doped synergist.
[0125] Comparative Example 11:
[0126] The difference from Example 3 is that the silicon carbide whisker liquid is replaced by silicon carbide whiskers.
[0127] The products of Examples 1 to 3 and Comparative Examples 1 to 11 were subjected to conventional performance tests, and the test results are as follows:
[0128]
[0129] The products of Examples 1 to 3 and Comparative Examples 1 to 11 were placed at -5°C for 12 hours, then at 60°C for 24 hours, and finally bent at a bending angle of 50 degrees, a bending frequency of 200 times / min, and 1000 times. The low temperature resistance and bending stability of the products were tested. The test performance is as follows:
[0130]
[0131] It can be seen from comparative examples 1-11 and examples 1-3 that the product of example 3 has excellent resilience, wear resistance and anti-slip performance, the performance of the product can achieve coordinated improvement, and the product has significant low temperature resistance and folding stability effects;
[0132] The present invention does not add any of the synergistic agents of the continuous strength regulator and the doped whisker, and the performance of the product deteriorates significantly, especially the low temperature resistance and the folding stability deteriorate significantly. The synergistic effect of the two is used, and the product performance effect is most obvious;
[0133] In the preparation of continuous strong adjustment, the flaky talc modifier is replaced by flaky talc, the preparation method of the flaky talc modifier is different, and the continuous adjustment liquid is not used in the preparation of continuous strong adjustment. The product performance has a tendency to deteriorate to varying degrees, especially if the continuous adjustment liquid is not used, the product performance deteriorates more significantly;
[0134] In the preparation of the whisker-doped synergist, the nano-silica synergist was not treated with nano-silica synergist, irradiated nano-silica was not added in the preparation of the nano-silica synergist, nano-bentonite was not added in the preparation of the nano-silica synergist, silane coupling agent KH560 was not added in the preparation of the nano-silica synergist, deionized water was used instead of chitosan solution, silicon carbide whisker liquid was not used in the preparation of the whisker-doped synergist, and silicon carbide whisker liquid was replaced with silicon carbide whiskers. The performance of the products showed a trend of deterioration. At the same time, nano-bentonite was not added, and the product performance stability deteriorated significantly. In addition, the nano-silica synergist and silicon carbide whisker liquids prepared by different methods showed a trend of deterioration in product performance effects. Only the nano-silica synergist and silicon carbide whisker liquids obtained by the method of the present invention had the most significant product performance effects. The effects of other methods were not as obvious as those of the present invention.
[0135] Based on the trend that the continuous effect regulating liquid has a greater impact on product performance, the present invention further explores it:
[0136] Experimental Example 1:
[0137] The only difference from Example 3 is that no boron nitride powder is added to the continuous effect regulating solution.
[0138] Experimental Example 2:
[0139] The only difference from Example 3 is that no sodium silicate solution is added to the continuous effect regulating solution.
[0140] Experimental Example 3:
[0141] The only difference from Example 3 is that no yttrium nitrate solution is added to the continuous effect regulating solution.
[0142] Experimental Example 4:
[0143] The only difference from Example 3 is that no glass fiber is added to the continuous effect regulating liquid.
[0144] Experimental Example 5:
[0145] The only difference from Example 3 is that sodium carboxymethyl cellulose is not added to the continuous effect regulating solution.
[0146] The low temperature resistance and folding resistance of the products in Experimental Examples 1 to 5 were tested, and the test performance results are as follows:
[0147]
[0148] It can be seen from Experimental Examples 1-5 that glass fiber is not added to the composition of the continuous-effect regulating liquid, and the performance changes of the product are most obvious in the composition factors of the continuous-effect regulating liquid, followed by the fact that boron nitride powder is not added. Therefore, the selection of the continuous-effect regulating liquid is proprietary. At the same time, it is also found that when sodium silicate solution is not added to the continuous-effect regulating liquid, yttrium nitrate solution is not added to the continuous-effect regulating liquid, and sodium carboxymethyl cellulose is not added to the continuous-effect regulating liquid, the performance of the product tends to deteriorate. Only when the continuous-effect regulating liquid composition of the present invention is used, the performance effect of the product is the most significant, and the use of other methods to replace the continuous-effect regulating liquid is not as significant as the effect of the present invention.
[0149] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0150] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A sole material, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of natural rubber, 25-30 parts of butadiene rubber, 7-11 parts of continuous strength adjuster, 4-7 parts of whisker-doped synergist, 3-5 parts of sulfur, 1-3 parts of carbon black, 1-3 parts of stearic acid, 1-3 parts of zinc oxide, 2-4 parts of antioxidant DPPD, and 2-4 parts of accelerator TMDM; The preparation method of the continuous strong effect agent is: S01: The flaky talc is first subjected to an oscillation treatment in a sufficient amount of a 5% by mass potassium permanganate solution at an oscillation power of 350-400 W for 20-30 min. After the oscillation is completed, the flaky talc is washed with water, filtered and dried to obtain a dry flaky talc; S02: 4-7 parts of dry flaky talc, 1-3 parts of urea, 2-3 parts of nano-silica sol and 5-8 parts of 5-7% sodium lignin sulfonate solution are mixed and stirred by weight, and after stirring, the mixture is washed with water, filtered and dried to obtain a flaky talc modifier; S03: Mix the flaky talcum powder modifier and the continuous effect regulating liquid in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1000-1500 r / min for 1-2 hours. After the ball milling is completed, wash with water and dry to obtain a continuous strong effect regulating agent; The continuous effect regulating solution comprises the following raw materials in parts by weight: 3~5 parts of boron nitride powder, 4~7 parts of yttrium nitrate solution, 2~5 parts of sodium silicate solution, 2~4 parts of glass fiber and 1~2 parts of sodium carboxymethyl cellulose; The preparation method of the synergist of the doped whisker is: S101: irradiating the nano-silicon dioxide in a proton irradiation box for 10-15 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-silicon dioxide after the irradiation is completed; Fully blend 2-5 parts of irradiated nano-silica, 1-3 parts of silane coupling agent KH560, 2-3 parts of nano-bentonite and 4-7 parts of chitosan solution by weight to obtain a nano-silica synergistic solution; S102: mixing silicon carbide whiskers with lanthanum nitrate solution at a weight ratio of 2:5 and stirring to obtain a silicon carbide whisker solution; S103: Mix the nano-silicon dioxide synergist liquid and the silicon carbide whisker liquid in a weight ratio of 2:5 and perform ball milling at a ball milling speed of 1500-1700 r / min for 1 hour. After the ball milling is completed, wash with water, filter, and dry to obtain a synergist doped with whiskers.
2. A sole material according to claim 1, characterized in that: The sole material comprises the following raw materials in parts by weight: 37.5 parts of natural rubber, 27.5 parts of butadiene rubber, 9 parts of continuous strength adjuster, 5.5 parts of whisker-doped synergist, 4 parts of sulfur, 2 parts of carbon black, 2 parts of stearic acid, 2 parts of zinc oxide, 3 parts of antioxidant DPPD, and 3 parts of accelerator TMDM.
3. A sole material according to claim 1, characterized in that: The mixing and stirring process has a stirring speed of 450-550 r / min, a stirring time of 35-45 min, and a stirring temperature of 50-55° C.
4. A sole material according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium silicate solution is 4-6%.
5. A sole material according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-6%.
6. A sports shoe sole, characterized in that: The shoe is made of the sole material according to any one of claims 1 to 5.
7. A sports shoe, characterized in that: Comprising the sports shoe sole as claimed in claim 6.
